(untitled) (AYUSHDHARA, 2025)
Rasayana therapy, a cornerstone of Ayurveda, the traditional Indian system of medicine, is a holistic regimen focused on rejuvenation, enhancing longevity, and improving overall health and resilience. Objective: This review aims to critically evaluate the scientific evidence supporting the potential of Rasayana therapy in the realms of cancer prevention and management of cancer survivorship issues, aligning its traditional principles with modern pharmacological and clinical findings. Methods: A narrative review of published literature was conducted using databases such as PubMed, Scopus, Google Scholar, and the AYUSH Research Portal. Search terms included "Rasayana," "Ayurveda cancer," "adaptogen," "immunomodulation," "antioxidant," "apoptosis," alongside specific herbs like Ashwagandha, Curcuma longa, Tinospora cordifolia, and Emblica officinalis. Results: Preclinical studies robustly demonstrate that key Rasayana herbs possess multifaceted anti-cancer properties, including potent antioxidant activity, induction of apoptosis, inhibition of angiogenesis and metastasis, modulation of detoxification enzymes, and enhancement of immune function. These effects are mediated through the regulation of key signalling pathways such as NF-κB, STAT3, and PI3K/AKT. Clinically, Rasayana therapy shows promise in improving the quality of life (QoL), reducing cancer-related fatigue, mitigating chemotherapy-induced toxicities (myelosuppression, neuropathy), and potentially enhancing chemoradiotherapy efficacy through radioprotective and chemosensitizing effects. Conclusion: Rasayana therapy presents a compelling, multi-targeted adjunctive approach in oncology. Its principles of enhancing host defense (Vyadhikshamatva) align with goals of preventing carcinogenesis and supporting survivors. While the existing evidence is promising, further high-quality, rigorous clinical trials are essential to standardize formulations, establish safety profiles, and integrate these ancient wisdom-based interventions into modern evidence-based oncologic care.